Chapter 14 Modeling and predicting future land use: Application of Dyna-CLUE and Cellular automata - Markov chain analysis (CA-Markov) models in a brazilian watershed - Demarchi, J.C. [UNESP]; Perusi, M.C. [UNESP]; dos Santos Galvanin, Edinéia Aparecida [UNESP]; Piroli, E.L. [UNESP] (Elsevier, 2025)
The prediction of future land use scenarios and the understanding of its dynamics are essential for environmental studies, especially in the context of climate change and the increase in human pressure on the environment. This chapter describes and analyzes the application of the CA-Markov and Dyna-CLUE models in simulating future land use and land cover (LULC) scenarios for the year 2030 in the São Domingos Stream watershed, located in the municipality of Santa Cruz do Rio Pardo, State of São Paulo, Brazil. A Markovian transition estimator was used to estimate the quantities of land use change based on data from previous periods. The models have different characteristics and cannot be directly compared. The simulated maps presented adequate LULC spatial patterns, considering the neighborhood component, and the models exhibited some advantages and limitations, which are discussed in the chapter.